Analisis Faktor Risiko Gastritis Pada Pasien Rawat Jalan di Puskesmas Bataraguru Kota Bau-bau - Mutia Ismail; Asriati Asriati; Wa Ode Salma (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Gastritis is a disease that can attack all levels of society from all levels of age and gender. This study aims to analyze the risk of Emotional Stress and the habit of consuming NSAIDs on the incidence of gastritis in outpatients in the working area of the Bataraguru Health Center, Baubau City. The case-control study involved 232 people in Baubau city, Wolio sub-district, Bataraguru sub-district, which were divided into 2 groups, namely 116 cases and 116 controls. The results of this study indicate that there is a relationship between emotional stress (p = 0.000) and the consumption of NSAIDs (p = 0.000). The conclusion of the study is that the way to avoid the occurrence of gastritis can be done by avoiding emotional stress and avoiding the consumption of NSAIDs.